From Unipolar to Bipolar: The Diagnostic Evolution in an Elderly Man - Lu, Vincent John Magat; Zhang, Melvyn Weibin; Tan, Giles Ming-Yee; Ying, Jiangbo (Case Reports in Psychiatry, 2023)
A pivotal concept in the field of mood disorders is the dichotomy between unipolar depression and bipolar disorder. Due to the unique treatment in older age bipolar disorder and the scarcity of research in this area, it is clinically important to raise the awareness of the diagnostic conversion of unipolar depression to bipolar disorder in the elderly population. We present a case of a 71-year-old Chinese man whose diagnosis was revised to bipolar disorder after 9 years of treatment for unipolar depression. Organic workup, including blood tests and brain imaging, was performed to rule out organic causes. This patient eventually responded well to the combined treatment of an antipsychotic and a mood stabilizer. This case report adds to the growing literature of challenges in identifying and managing bipolar disorder in the elderly. As unipolar depression and bipolar disorder have different disease courses and different treatment strategies, it is essential for clinicians to be aware of diagnostic conversion. Further research is needed to delineate bipolar disorder from unipolar depression in the elderly population.